OPTIMIZING INVESTMENT DECISIONS USING A REAL OPTIONS-BASED PROJECT EVALUATION MODEL: IMPLEMENTATION IN THE RENEWABLE ENERGY SECTOR - Loso Judijanto; Bambang Sugeng Dwiyanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Investments in the renewable energy sector face the challenge of high uncertainty due to energy price volatility, regulatory changes and technological developments. Traditional investment evaluation methods such as Net Present Value (NPV) and Internal Rate of Return (IRR) are often less effective in dealing with these dynamics because they do not consider flexibility in decision making. Therefore, the Real Options approach emerged as an alternative solution that allows investors to adjust investment strategies based on changing market conditions. This research is a literature review which aims to analyze the effectiveness of Real Options in optimizing investment decisions in the renewable energy sector. Through literature studies from journals, academic books, and research reports, comparisons were made between traditional methods and Real Options, as well as identification of key factors that influence the application of this model, such as government policy, technological innovation, and access to funding. This study shows that the Real Options approach provides advantages in managing risk, increasing the flexibility of investment strategies, and optimizing project value by considering strategic options such as delaying, expanding, or canceling projects. The results of this research have important implications, both theoretically and practically. Theoretically, this research reinforces the concept that investment must be dynamic and adaptive, especially in an environment full of uncertainty such as renewable energy. Practically, applying this model can help investors optimize investment decisions and reduce financial risk. However, challenges such as the complexity of calculations and limited access to accurate data are still obstacles in its implementation. Therefore, it is necessary to develop simpler analytical tools and more stable policies to support Real Options-based renewable energy investment.